Analysis of the Influence of Product Quality and Product Uniqueness on the Purchasing Decision of Onde Mutiara in Medan City - Novita, Febby; Limurti, Wilson; Godwin, Gerry (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the influence of product quality and product uniqueness on purchasing decisions for Onde Mutiara in Medan City. A non-parametric quantitative approach was employed by distributing questionnaires to 110 respondents. The data were analyzed using Spearman correlation and ordinal logistic regression. Results indicate that product quality and uniqueness have a positive and significant effect on consumer purchasing decisions. These findings show that both variables can enhance loyalty and buying interest. The implications suggest strategic input for local culinary MSMEs to focus on improving product quality and differentiation to strengthen competitiveness and increase market interest effectively.